2014
DOI: 10.3989/scimar.03995.28b
|View full text |Cite
|
Sign up to set email alerts
|

Mobile epifaunal assemblages associated with <em>Cystoseira</em> beds: comparison between areas invaded and not invaded by <em>Lophocladia lallemandii</em>

Abstract: Summary:The study compared the structure of mobile epifaunal assemblages associated with Mediterranean Cystoseira beds between areas invaded and not invaded by Lophocladia lallemandii. A total of 150 taxa were identified: 42 Polychaeta, 78 Arthropoda, 26 Mollusca and 4 Echinodermata. Epifaunal assemblages differed between areas invaded and not invaded by Lophocladia lallemandii when the invasive species reached maximum values of cover and biomass, while differences between conditions were not significant in ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 47 publications
1
5
2
Order By: Relevance
“…The examined molluscan assemblage included a relatively high number of taxa 52belonging to three different classes and quite diverse trophic groups. These results are generally in agreement with previous studies (Zavodnik 1965;Bellan-Santini 1969;Kocatas 1978;Chemello 1986;Menioui 1992a;Chemello and Milazzo 2002;Lolas et al 2018), as the number of molluscan species reported as living within Cystoseira beds usually varied from ~20 (Bellan-Santini 1962, 1964, 1969Ergen and Çinar 1994;Russo 1997;Bedini et al 2014) to ~70-100 (Poulicek 1985;Pitacco et al 2014;Piazzi et al 2018), with extreme values of five taxa reported by Mačić and Svirčev (2014) and 161 taxa reported by Milazzo et al (2000). The former study, however, only investigated macro-epiphytes, whilst the latter one investigated photophilic assemblages as a whole, although largely dominated by Cystoseira.…”
Section: Molluscan Assemblage Associated With Cystoseira Algae At Iscsupporting
confidence: 92%
See 1 more Smart Citation
“…The examined molluscan assemblage included a relatively high number of taxa 52belonging to three different classes and quite diverse trophic groups. These results are generally in agreement with previous studies (Zavodnik 1965;Bellan-Santini 1969;Kocatas 1978;Chemello 1986;Menioui 1992a;Chemello and Milazzo 2002;Lolas et al 2018), as the number of molluscan species reported as living within Cystoseira beds usually varied from ~20 (Bellan-Santini 1962, 1964, 1969Ergen and Çinar 1994;Russo 1997;Bedini et al 2014) to ~70-100 (Poulicek 1985;Pitacco et al 2014;Piazzi et al 2018), with extreme values of five taxa reported by Mačić and Svirčev (2014) and 161 taxa reported by Milazzo et al (2000). The former study, however, only investigated macro-epiphytes, whilst the latter one investigated photophilic assemblages as a whole, although largely dominated by Cystoseira.…”
Section: Molluscan Assemblage Associated With Cystoseira Algae At Iscsupporting
confidence: 92%
“…Molluscan assemblages associated with Cystoseira beds have been the subject of studies in several regions from the western to the eastern Mediterranean since the mid-1900s, due to the recognized importance of these canopy-forming algae in shaping and supporting local biodiversity (Bellan-Santini 1962, 1964, 1969Zavodnik 1965;Kokataş 1978;Tiganus 1984;Poulicek 1985;Chemello 1986;Menioui 1992aMenioui , 1992bErgen and Çinar 1994;Russo 1997;Milazzo et al 2000;Chemello and Milazzo 2002;Bedini et al 2014;Mačić and Svirčev 2014;Pitacco et al 2014;Lolas et al 2018;Piazzi et al 2018). In the Gulf of Naples, however, the historically most investigated habitat-forming species were Posidonia oceanica (Linnaeus) Delile and Cymodocea nodosa (Ucria) Ascherson (Russo et al 1983;Mazzella et al 1989Mazzella et al , 1992; Gambi et al 1992Gambi et al , 1996Scipione et al 1996;Gambi 2002), with few recent exceptions represented by Corallinales taxa and Sargassum vulgare (Agardh) (Massa-Gallucci et al 2006; Chiarore and Patti 2013).…”
Section: Molluscan Assemblage Associated With Cystoseira Algae At Iscmentioning
confidence: 99%
“…Interestingly, our results highlight that A. taxiformis affected each component (molluscs, annelids and amphipods) of the epifaunal assemblages in the same way. This is in contrast with other studies that showed different responses among epifaunal components associated to invasive seaweeds (Schmidt and Scheibling, 2006;Gestoso et al, 2010;Guerra-García et al, 2012;Bedini et al, 2014;Veiga et al, 2018;Navarro-Barranco et al, 2019). For example, species richness, Shannon diversity and total abundance of isopods were signi cantly lower in A. armata compared to native algae (Guerra-García et al, 2012).…”
Section: Discussioncontrasting
confidence: 80%
“…ecological role of these foundation species is of major importance as they are autogenic engineers (Schiel and Foster, 1986;Thomsen et al, 2010;Wernberg et al, 2011) and provide much of the three-dimensional structure habitat and food resources for associated organisms (Mann, 1973;Dayton, 1985;Bedini et al, 2014). The main large brown canopy forming macroalgae belong to the orders Laminariales s.l.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A reduction of the frond size in Cystoseira abies-marina from Canary Islands has been recorded in the past decades analysing herbarium specimens from a long temporal series (Sansón et al, 2013). A decrease of C. baccata forest could impact the nursery value for littoral fishes, particularly during the recruitment period (Cheminée et al, 2013) and mobile fauna (Bedini et al, 2014).…”
Section: Response Variablesmentioning
confidence: 99%